ANALYSIS OF VARIATION OF SOUND CHANGES IN ARABIC LANGUAGE PHONEMES IN JUNIOR HIGH SCHOOL STUDENTS IN JAVA, INDONESIA (Lisanul Arab: Journal of Arabic Learning and Teaching, 2023)
The purpose of this study was to determine the variation of Arabic sounds pronounced by 8th-grade junior high school students in Java, Indonesia. The method used in this study uses a qualitative method with descriptive analysis with the research subject of 8th-grade junior high school children in Java, Indonesia. The results of the study found variations in sound changes in 8th-grade middle school children in Java, Indonesia.